(untitled) (diségno, 2024)
One of the most challenging aspects of the architectural project is the representation of the landscape, particularly when dealing with the graphic representation of abrupt natural enclaves. In the field of contemporary architecture, technical documentation often employs abstractions to illustrate the relationship between construction and landscape in a synthetic way. The terrain is conceptualized using contour lines, and the vegetation, paths while other elements of the site are simplified to highlight the position of the intervention. Notwithstanding the aforementioned general tendency, the figures of Dimitris Pikionis (Athens, 1887-1968) and Alberto Ponis (Genoa, 1933-) stand out as two architects who have distanced themselves from these conventional tendencies of representation by virtue of their faithful definition of the landscape. Their projects, situated in the Mediterranean basin, are characterized by the topographical complexity to which they adapt. It is therefore crucial to understand their particular graphic approach in order to fully comprehend the development and subsequent understanding of their interventions. In this context, the landscape representations used by Pikionis and Ponis in the Xenia Hotel (Delphi, 1951-56) and Casa Hartley (Costa Paradiso, 1977) projects are analyzed as paradigmatic models, demonstrating, through their graphics an exceptional approach, to safeguard the landscape through the harmonious integration of natural and man-made elements.